Huge spring migrations of insects from the Middle East to Europe: quantifying the migratory assemblage and ecosystem services. Issue 10 (19th August 2022) - Hawkes, Will L. S.; Walliker, Edward; Gao, Boya; Forster, Olivia; Lacey, Katharine; Doyle, Toby; Massy, Richard; Roberts, Nicholas W.; Reynolds, Don R.; Özden, Özge; Chapman, Jason W.; Wotton, Karl R.
Abstract : Migratory insects are a key component of terrestrial ecosystems, but understanding their full contribution is challenging as they are difficult to track, and migration often takes place at high altitude. Migration hotspots offer an exceptional opportunity to study these otherwise indiscernible movements as migration can be visible at ground level; however these events are often also ephemeral and reported only from chance encounters. It is therefore often difficult to fully characterise the range and number of species involved, the drivers of migration or to appreciate the potential interactions and ecological roles of the migrants. Here we pursue field evidence suggesting that the Karpaz peninsula in northeast Cyprus is a suitable location to systematically collect data on migratory insects. In the spring of 2019, using a combination of timed‐counts, migration‐camera traps and netting we documented over 39 million day‐flying insects from eight orders arriving on Cyprus at rates of up to 5900 insects m ‐1 min ‐1 . Mass arrivals were correlated with higher temperatures and easterly winds. Wind direction and normalised vegetation difference index (NDVI) data suggest that these insects had their natal origins in locations including Syria, Iraq and Saudi Arabia. It is estimated that many billions of insects left the coast of the Middle East heading west into Europe during the study period. While the migrant assemblage was diverse, Diptera were by far the most numerous insect order (86%) followed by Lepidoptera (10%). These migrating insects play a range of vital ecological roles including cross‐continental pollination and the transfer of important nutrients. We believe that the very infrequently explored processes described in this manuscript have important consequences for ecosystems in the destinations of these migratory insects across Europe.